HUBUNGAN PENDAPATAN DAN POLA ASUH ORANG TUA DENGAN KEJADIAN STUNTING PADA BALITA - Nurdiyanti, Siti Haliza; Fetriyah, Umi Hanik; Ariani, Malisa; Latifah, Hj (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2024)
Background: Stunting is a condition of toddlers who suffer from chronic malnutrition due to failure to thrive which causes metabolic disorders, decreased IQ, and reduces future productivity. There are many factors that influence nutritional needs, such as income and parenting patterns, which can influence the incidence of stunting. Objective: To determine the relationship between parental income and parenting patterns with the incidence of stunting among toddlers at the Pekauman Community Health Center, Banjarmasin. Method: Quantitative research type, cross sectional design. The total sample was 103 parents and toddlers. Accidental sampling technique. Data collection techniques used questionnaires and anthropometric examinations, and analyzed using the Chi Square test. Results: Most of the toddlers aged 48-60 months were 62 people (60%), 53 people were female (51%). Most of the parents of toddlers were aged ≥20 as many as 103 people (100%). Most parents have low incomes, 75 people (73%), and some of them apply a permissive parenting style, 46 people (45%). Analysis of the incidence of stunting in toddlers is 62%. The results of the analysis of the relationship between income and the incidence of stunting are p-value=0.075 and p-value=0.312 for the relationship between parenting styles and the incidence of stunting. Conclusion: The P value shows a value of more than 0.05, which means there is no relationship between parental income and parenting patterns with the incidence of stunting in toddlers. However, parents of toddlers are expected to always monitor their weight and height every month to reduce the risk of stunting.